Integrasi Teknologi dalam Pembelajaran PAI untuk Meningkatkan Kualitas Pembelajaran di SDN 1 Kecila - Mr, Yazid Abdul Qadir Jawaz; Hanif, Muh. (IAI Nasional Laa Roiba Bogor, 2024)
This research explores the integration of technology in Islamic Education (Pendidikan Agama Islam) learning at SDN 1 Kecila. In the digital era, the use of technology in education has become a necessity, including at the elementary level. This integration has the potential to enhance the effectiveness and efficiency of learning by improving concept comprehension, student engagement, and digital skill development. The study aims to identify strategies, benefits, and challenges of technology integration in Islamic Education as well as its practical implications. Constructivist theory suggests that technology can enrich students' interactions with learning materials, while competency-based learning and cooperative learning theories emphasize the development of students' abilities through feedback and collaboration. The results of this study (Odden, 1991, hlm. 76)are expected to provide insights for educational decision-makers in improving the quality of Islamic Education learning in elementary schools. Technology integration is expected to enhance learning quality, student engagement, and material accessibility, as well as support the balanced development of students' spiritual, social, and intellectual competencies.